Remote monitoring of rural water systems: A pathway to improved performance and sustainability?. (25th December 2020) - Thomson, Patrick
Abstract: The presence of the mobile phone network in rural areas where there is little other infrastructure has opened up the prospect of automatically monitoring rural water systems, something previously possible only in person and perhaps only on foot. The technology to monitor these systems continues to develop: basic systems are now leaving research and being implemented in operational WASH programs; machine learning is making pump failure prediction possible. With the move from the previous infrastructure‐focused community management paradigm, to a service‐delivery approach to rural water, remote monitoring has salience with its potential to inform professional maintenance services. This is not without cost. To justify its use in rural water service delivery remote monitoring must generate benefits for service providers: (1) it must be integrated into management systems, and help redesign them; (2) it must contribute to increases in performance that produce real improvement in outcomes for water users; (3) it must open up new transparent sources of funding previously unavailable to the rural water sector. If remote monitoring can do these three things it has a role to play in achieving SDG 6.1; if not it will join the list of development techno‐fixes that failed to make an impact despite the best of intentions. This article is categorized under: Human Water > Human Water Abstract : An automatically monitored handpump in Kenya being repaired by a professional mechanic.